Model Pembelajaran Menulis Bahasa Indonesia yang Berorientasi pada Kompetensi Literasi - Anita Candra Dewi; Erwin Eka Saputra (Journal of Humanities, Social Sciences, and Education, 2025)
Literacy competency is an essential skill in 21st-century education, and writing skills, as part of basic literacy, play a crucial role in enhancing students' critical thinking and expressive abilities. This study aims to examine various Indonesian writing learning models oriented toward strengthening literacy competency in schools. Through a literature review of 20 scientific articles, reference books, and research findings from the past five years, it was found that learning approaches focused on active student engagement, the use of digital media, and the contextualization of students' personal experiences demonstrate significant results in improving writing and literacy skills across the board. Five dominant learning models were identified: project-based learning, genre-based learning, process-based writing, digital literacy-based learning, and collaborative learning. The study's results demonstrate that integrating learning models relevant to students' needs and contexts is crucial in supporting the development of writing literacy. This study recommends the use of models that accommodate diverse learning styles and provide reflective space for students to write authentically. These findings can serve as a reference for teachers, education practitioners, and curriculum developers in designing more effective and literate Indonesian writing learning strategies.